Property as national security - Erie, M (University of Wisconsin at Madison, 2024)
Two historically disparate fields of law—property and national security—are colliding through the hyper-activity of state governments. Against the backdrop of the U.S.-China trade/tech war, state governors and legislatures are competing with each other in introducing bills to sever all ties with China, stunt the growth of Sinocentric supply chains, and neutralize China’s soft power in the world. While the state bills operate in parallel to federal legislation and regulation, in many instances, states’ activities go much further than federal efforts. States are laboratories of China-delinking. The China-related bills passed to date address a wide range of subjects: from TikTok and semiconductors, to educational exchange and Confucius Institutes, to human rights and forced labor in Xinjiang. National security is often the justification for these laws. While the state statutes have strong symbolic aspects, they are already affecting property relationships, and raise a host of constitutional and foreign affairs questions. These issues have galvanized litigation that is currently working its way through the federal court system. The infusion of national security into property law has potentially far-reaching consequences not only for Chinese citizens residing in the U.S. and for U.S.-China relations, but also for the future development of American property law.